The legal language. Contributions to the characterization of the Legal Codes - Carapinha, Conceição (2018)
Law is a heterogeneous domain, in which there are different texts and multiple discourses, stemming from different authors, addressed to different recipients, in very different contexts. ‘Legal language’ is a generic term which therefore encompasses distinct legal languages, languages whose specificity, complexity and interrelation have only recently attracted researchers. Starting from the notions of ‘register’ and ‘genre’, the present work tests a possible definition of the concept of legal language and characterizes a particular juridical genre: the Civil Code and the Penal Code in force in the Portuguese legal system, reviewing some of the lexical, morphological, syntactic-semantic and textual traits that are exhibited by this genre. The analysis of this textual genre shows that the internal structuring of these texts reflects the communicative purposes and the organizational objectives of the professional community that uses these Legal Codes. This study also contributes to the discussion around the different legal genres.